Language and Forensic Linguistics - Paramita Kusumawardhani (International Journal of English and Applied Linguistics (IJEAL), 2024)
Language which consists of some aspects such as semantics, syntax, morphology, phonology, pragmatics, phonetics, lexicology, discourse semantics and other linguistic elements can be found in legal cases. As the language develops dynamically then it has a unique dimension that requires special studies. This study aims to discuss aspects of the language used for forensic linguistics. The discussion is also enriched with references to several studies to show potential that can be explored more deeply. The method used in this study is a descriptive method because this study focuses on the language in forensic linguistics. The instruments used in this research are some cases which had happened. The results of this study indicate that the forensic linguistics is present as a tool in the judiciary to assist in studying speech that appears with the contexts of the speech that occurred. The task of linguists in this case is very necessary in analyzing the things that are in this linguistic aspect. A linguist cannot determine guilt or innocence or assign punishment to the perpetrator, but a linguist can provide linguistic evidence related to the case.